Pre-Travel Vaccinations and Malaria Prophylaxis for International Travelers - Androula Pavli; Helena C. Maltezou (Public Health, 2017)
International travel has increased dramatically the past decades, potentially posing health risks at the level of traveler and the level of public health. Vaccine-preventable diseases and malaria constitute a non-negligible proportion of imported infectious diseases to developed countries. This is a short review of pre-travel advice regarding vaccination and malaria prophylaxis for international travelers to developing countries. Vaccination and malaria prophylaxis depend on a risk-benefit analysis, weighting the risk of the disease against the risk of possible side effects of the vaccine or antimalarial agent. Recommendations for vaccination and malaria prophylaxis are based on the epidemiological situation at destination, travel’s (e.g., destination, purpose and duration of travel) and traveler’s (e.g., demographics, medical history and past vaccinations) characteristics. Recommendations of vaccination and malaria prophylaxis should be based on selective and individualized risk assessment. Public health authorities should increase awareness of travelers and health professionals for travel related health issues in order to prevent travel-associated vaccine-preventable diseases and malaria and promote safety both for the traveler as well as for the community.